Hemolytic Anemia and Reactive Thrombocytosis Associated With Cefoperazone/Sulbactam - Zhou, Ling; Bao, Jianan; Ma, Jingjing (Frontiers in Pharmacology, 2019)
Background: Cefoperazone/sulbactam is a broad-spectrum antibacterial agent. Drug-induced immune hemolytic anemia is a rare but serious condition, and reactive thrombocytosis is caused by processes extrinsic to the megakaryocyte. Limited data are available for cefoperazone/sulbactam-associated hemolytic anemia and reactive thrombocytosis. Case presentation: We report the case of a 60-year-old woman undergoing surgical excision of the left atrial myxoma, who presented with hemolytic anemia and thrombocytosis following cefoperazone/sulbactam administration for lung infection. The duration of cefoperazone/sulbactam therapy was 8 days. Blood analysis showed markedly decreased hemoglobin, hematocrit, and red blood cell levels, with elevated lactate dehydrogenase, indirect bilirubin, platelets, and reticulocytes. Furthermore, the direct antiglobulin test was positive for anti-C3 and a diagnosis of hemolytic anemia and reactive thrombocytosis was made. Then, cefoperazone/sulbactam was discontinued and red blood cell transfusion was performed for three days. After one week, the patient’s condition improved, and she was discharged. Conclusion: This is the first suspected case report of immune hemolytic anemia and reactive thrombocytosis related to cefoperazone/sulbactam. Caution should be taken for this reaction in patients undergoing cefoperazone/sulbactam therapy.